Theoretical modeling and numerical simulation of seismic motions at seafloor - Li, C.; Hao, Hong; Li, H.; Bi, Kaiming (Pergamon, 2015)
This paper proposes a modelling and simulation method of seafloor seismic motions on offshore sites, which are composed of the base rock, the porous soil layers and the seawater layer, based on the fundamental hydrodynamics equations and one-dimensional wave propagation theory. The base rock motions are assumed to consist of P- and S-waves and are modelled by the seismological model in southwest of Western Australia (SWWA). The transfer functions of the offshore site are calculated by incorporating the derived dynamic-stiffness matrix of seawater layer into the total stiffness matrix. The effect of water saturation on the P-wave velocity and Poisson’s ratio of subsea soil layers are also considered in the model. Both onshore and seafloor seismic motions are stochastically simulated. The comparison results show that the seafloor vertical motions are significantly suppressed near the P-wave resonant frequencies of the upper seawater layer, which makes their intensities much lower than the onshore vertical motions. Owing to their compliance with the characteristics of available seafloor earthquake recordings, the proposed method can be used to simulate seafloor motions for offshore structural seismic analyses.